Perencanaan Jembatan Baja Sederhana dan Perencanaan Penahan Tanah Menggunakan Beronjong pada Areal Rumahku Hijau Sukabumi - Sudarsono, Ignatius; Mulyawati, Fauzia; Marhamatunnisya, Alfhi; Mulya, Todo; ., Andriansyah; Sugandi, Diki kirana; Al Fiqry, Bangga Futra; Amelia, Riri; Fallah, Rahmi; Ramadhan, Elkhi Seftiarki; Ikhsan, Iqbal Irvani; Ramadhan, Gilang; Ramadhan, Yanuarko; Gumilar, Gugum; Wahyudi, Dwi Agung (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2022)
The location of Rumahku Hijau is located in Cikaret Village, Cipedes District, Sukabumi Regency, West Java. Rumahku Hijau is engaged in plant cultivation, manufacture of organic fertilizers, manufacture of organic pesticides. Rice fields and animal cultivation areas such as birds, rabbits, goats and others. During the visit there were several problems, namely landslides and it was difficult for farmers to bring their agricultural products to the barn, because of the location of the rice fields and barns which were separated by the Cidadap river. That way, in carrying out this community service, we want to design a simple steel bridge and use gabion to overcome landslides. It is hoped that farmers will not have to go around the Cidadap river to reach the barn and be safe from landslides.